Distribution and diversity of anaerobic thermophiles and putative anaerobic nickel-dependent carbon monoxide-oxidizing thermophiles in mesothermal soils and sediments - DePoy, Amber N.; King, Gary M. (Frontiers in Microbiology, 2023)
Even though thermophiles are best known from geothermal and other heated systems, numerous studies have demonstrated that they occur ubiquitously in mesothermal and permanently cold soils and sediments. Cultivation based studies of the latter have revealed that the thermophiles within them are mostly spore-forming members of the Firmicutes. Since the geographic distribution of spores is presumably unconstrained by transport through the atmosphere, similar communities (composition and diversity) of thermophiles might be expected to emerge in mesothermal habitats after they are heated. Alternatively, thermophiles might experience environmental selection before or after heating leading to divergent communities. After demonstrating the ubiquity of anaerobic thermophiles and CO uptake in a variety of mesothermal habitats and two hot springs, we used high throughput sequencing of 16S rRNA genes to assess the composition and diversity of populations that emerged after incubation at 60 ˚C with or without headspace CO concentrations of 25%. Anaerobic Firmicutes dominated relative abundances at most sites but anaerobic thermophilic members of the Acidobacteria and Proteobacteria were also common. Nonetheless, compositions at the amplicon sequence variant (ASV) level varied among the sites with no convergence resulting from heating or CO addition as indicated by beta diversity analyses. The distinctions among thermophilic communities paralleled patterns observed for unheated “time zero” mesothermal soils and sediments. Occupancy analyses showed that the number of ASVs occupying each of n sites decreased unimodally with increasing n; no ASV occupied all 14 sites and only one each occupied 11 and 12 sites, while 69.3% of 1873 ASVs occupied just one site. Nonetheless, considerations of distances among the sites occupied by individual ASVs along with details of their distributions indicated that taxa were not dispersal limited but rather were constrained by environmental selection. This conclusion was supported by MNTD and NTI analyses, which showed dispersal limitation was only a minor contributor to taxon distributions.